Perioperative outcome of patients with congenital diaphragmatic hernia undergoing open versus minimally invasive surgery - Szavay, Philipp O; Obermayr, Florian; Maas, Christoph; Luenig, Holger; Blumenstock, Gunnar; Fuchs, Joerg (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2012)
The aim of this study was to evaluate outcome of patients with congenital diaphragmatic hernia (CDH) undergoing open versus minimally invasive surgery. Patient records of 33 children undergoing surgery for CDH between March 2002 and September 2008 were reviewed. Patient data were compared regarding operating time, intraoperative maximum CO(2) partial pressure (pCO(2 max)) values, postoperative ventilation time, complications, and recurrences. Median age at time of operation was 4 days (range, 0-1017 days), and median weight was 3800 g (range, 2000-13,200 g). Laparotomy was performed in 12 children. Seventeen patients underwent thoracoscopic repair, and four children had a laparoscopic approach. Operating time was significantly longer (P=.004) in the minimally invasive group. Median values of pCO(2 max) during operation were not significantly different (P=.25) in the minimally invasive surgery group. The pCO(2 max) values in the postoperative course were significantly lower (P=.013) in the minimally invasive group, whereas median ventilation times postoperatively were significantly longer (P=.024) in the open surgery group. Median values of pCO(2 max) in the postoperative course were significantly lower in the minimally invasive surgery group. In addition, postoperative ventilation time was shorter when children underwent minimally invasive surgery. In conclusion, minimally invasive surgery seems to offer advantages for selected patients with CDH.